PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN PENELITIAN TINDAKAN KELAS (PTK) MELALUI METODE DISKUSI DI SD SEKECAMATAN PURBOLINGGO - Uswatun Khasanah; Iskandar Jalaludin; Eka Noviana (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2017)
The purpose of this class action research is to describe the improvement in the ability of teachers in developing classroom action research (CAR) through the use of discussion methods in elementary schools in Purbolinggo district. This type of research is School Action Research. The model used is a spiral model with research procedures consisting of action planning, action implementation, observation, and reflection. The study was conducted through two cycles of action. Data collection methods used were nontest, test, observation, which was conducted by researchers with colleagues. In analyzing the research data used a qualitative descriptive method which is assisted with the calculation of percentages. Based on the results of the study can be described that in the activities of the first cycle after the discussion method used the ability of teachers in preparing the CAR is less satisfactory. Of the four teacher groups, two groups (50%) had good grades and the other two groups (50%) had poor grades. In addition, the ability of teachers to understand the preparation of PTK individually in Cycle I was also unsatisfactory. Of the 9 teachers as many as 5 people (55.6%) had the ability to understand the preparation of PTK individually was good, while 4 people (44.4% ) lack of ability. In this regard, the researchers repeated the improvement activities in the second cycle. The results of the second cycle showed that the ability of teachers experienced a satisfactory increase. Of the 4 groups of teachers who have the ability to compile a CAR with grades> 80 (good) totaling 3 groups (75%), while those with a value of 75 (enough) are 1 group (25%). Individually the ability of teachers to understand how to prepare CAR is also satisfactory. From 9 teachers as many as 7 people (77.8%) have the ability to understand the preparation of PTK individually is good, while 2 people (22.2%) ability is still lacking. From the results of the above study it can be concluded that the ability of teachers in compiling classroom action research (CAR) in elementary schools in Purbolinggo can be improved through the use of discussion methods.